Laboratory evaluation on effect of groundnut shell ash on performance parameters of asphalt binder and mixes. Issue 6 (17th August 2020) - Arabani, Mahyar; Esmaaeli, Niloofar
Abstract : Ideas of reducing disposal problems, contributing to the conservation of natural resources, helping with recycling, and also improving the performance of pavements have led researchers to use agricultural waste in asphalt pavements. Groundnut shell is a type of high-volume agricultural waste generally burned in order to produce energy or as means of disposal. The present study examined the effect of using groundnut shell ash (GSA) as an asphalt binder modifier on the properties of hot mix asphalt (HMA). GSA was added to binder at different concentrations of 5, 10, 15, and 20% in terms of total asphalt binder weight. Various tests, including conventional asphalt tests, high temperature storage stability, rotational viscosity (RV), dynamic shear rheometer (DSR), and bending beam rheometer (BBR) tests were performed to determine the properties of the modified asphalt binder. Also, Marshall, indirect tensile stiffness modulus (ITSM), repeated load axial (RLA), and indirect tensile fatigue (ITF) tests were conducted to assess the mechanical performance of the HMA mixes. Test results revealed that asphalt binder modified with up to 10% GSA remained stable during high temperature storage. In addition, an increase in the softening point, viscosity, and rutting resistance as well as a reduction in the penetration grade, ductility, and fatigue and low-temperature cracking resistance was observed following the addition of GSA to the asphalt binder. Besides, it was proven that modification with GSA enhanced the mechanical performance of asphalt mixtures.